Сучасний погляд на систему суб’єктів протидії злочинності - Бутенко, В. Б.; Butenko, V. B. (Європейські перспективи. - 2021. - № 3. – С. 115-120, 2021)
Проведено системно-структурний аналіз суб’єктів протидії злочинності як базової кримінологічної категорії. Аргументовано доцільність розгляду суб’єктів, що діють у сфері протидії злочинності в якості соціально обумовленої ієрархічної системи. Доведено, що системний підхід до вирішення цього питання дозволяє визначити місце і роль вказаних суб’єктів у загальній структурі протидії злочинності, окреслити їх функціональні зв’язки, подолати можливе дублювання виконуваних функцій, за необхідності посилити вплив на певний сегмент криміногенних факторів. Проаналізовано роль громадян як автономних суб’єктів протидії злочинності. Визначено доцільність включення громадян до системи суб’єктів протидії злочинності через категорію громадянськості, яку в аналізованому аспекті пропонується розуміти як внутрішнє сумлінне ставлення особи до виконання свого громадського обов’язку у сфері протидії злочинності.

The purpose of the article is to elaborate authorial notions of subjects of crime counteraction and a system of subjects of crime counteraction as basic criminological categories that must meet the demands of modernity. Basing on the works of domestic and foreign criminologists the article conducts systematic-structural analysis of the subjects of crime counteraction as basic criminological categories. It defines and analyses two main scientific approaches to understanding of the subjects of crime counteraction as an aggregation of subjects of crime counteraction and as a system of the subjects of crime counteraction. The article ascertains appropriateness of reviewing the system of the subjects of crime counteraction as a socially stipulated hierarchical system with a set of vertical (subordinate) and horizontal (coordination) interconnections which provide premises for its effective functioning and potential for selfenhancement and self-control. It provides arguments that systematic approach to this issue allows to establish the place and role of a subject of crime counteraction in the structure of system analyzed, to define its functional connections and provides possibility to eliminate overlapping functions, exacerbate influence at a certain criminogenic factor, if necessary. The article analyzes the role of citizens as autonomous subjects of crime counteraction. It promotes appropriateness of including citizens to the system of subjects of crime counteraction through the category of publicity that in the present context is viewed as a subjective diligent attitude towards personal obligation in the sphere of crime counteraction. Based on the conducted analysis the article elaborates scientific notions of the subjects of crime counteraction and the system of subjects of crime counteraction.

Проведено системно-структурний аналіз суб’єктів протидії злочинності як базової кримінологічної категорії. Аргументовано доцільність розгляду суб’єктів, що діють у сфері протидії злочинності в якості соціально обумовленої ієрархічної системи. Доказано, что системный подход к решению этого вопроса позволяет определить место и роль указанных субъектов в общей структуре противодействия преступности, определить их функциональные связи, преодолеть возможное дублирование выполняемых функций, при необходимости усилить влияние на определенный сегмент криминогенных факторов. Проанализирована роль граждан как автономных субъектов противодействия преступности. Определена целесообразность включения граждан в систему субъектов противодействия преступности через категорию гражданственности, которую в рассматриваемом аспекте предлагается понимать как внутреннее добросовестное отношение личности к выполнению своего общественного долга в сфере противодействия преступности.
Бутенко, В. Б. Сучасний погляд на систему суб’єктів протидії злочинності / Бутенко Віктор Борисович // Європейські перспективи. - 2021. - № 3. – С. 115-120. - DOI: 10.32782/EP.2021.3.17.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; протидія злочинності; crime prevention; противодействие преступности; суб'єкти протидії злочинності; subjects of crime prevention; субъекты противодействия преступности; система суб’єктів протидії злочинності; system subjects of crime prevention; система субъектов противодействия преступности; громадяни; громадянський обов’язок; civic duty; гражданский долг; громадянський контроль; civil control; гражданский контроль